Risks of Intracochlear Pressures From Laser Stapedotomy. Issue 3 (March 2020) - Misch, Emily S.; Banakis Hartl, Renee M.; Gubbels, Samuel P.; Greene, Nathaniel T.
Abstract : Hypothesis: Surgical manipulations during laser stapedotomy can produce intracochlear pressure changes comparable to pressures created by high-intensity acoustic stimuli. Background: New-onset sensorineural hearing loss is a known risk of stapes surgery and may result from pressure changes from laser use or other surgical manipulations. Here, we test the hypothesis that high sound pressure levels are generated in the cochlea during laser stapedotomy. Methods: Human cadaveric heads underwent mastoidectomy. Fiber-optic sensors were placed in scala tympani and vestibuli to measure intracochlear pressures during key steps in stapedotomy surgery, including cutting stapedius tendon, lasering of stapedial crurae, crural downfracture, and lasering of the footplate. Results: Key steps in laser stapedotomy produced high-intensity pressures in the cochlea. Pressure transients were comparable to intracochlear pressures measured in response to high intensity impulsive acoustic stimuli. Conclusion: Our results demonstrate that surgical manipulations during laser stapedotomy can create significant pressure changes within the cochlea, suggesting laser application should be minimized and alternatives to mechanical downfracture should be investigated. Results from this investigation suggest that intracochlear pressure transients from stapedotomy may be of sufficient magnitude to cause damage to the sensory epithelium and affirm the importance of limiting surgical traumatic exposures.